Back contact solar cell electrode interface structure based on carbon-based seed layer and method of manufacturing the same

CN122995338APending Publication Date: 2026-10-27TIANJIN ZHONGHUAN SEMICON CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611247499.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-17
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0003]然而,现有技术仍存在以下不足:(1)种子层材料选择受限:目前主流种子层仍以银浆为主,成本压力突出;镍、铜等贱金属种子层虽有探索,但镍存在内应力大、孔隙率高、热膨胀系数与硅不匹配等问题;钛虽具备良好导电性、耐腐蚀性,能与硅形成低阻硅化物,并可作为铜扩散阻挡层,但其在空气中极易氧化生成高阻氧化层,导致难以通过常规印刷烧结工艺制备,更无法满足电镀种子层对表面导电性与活性的严苛要求

Benefits of technology

本发明提供的基于碳基种子层的背接触太阳能电池电极界面结构,所述电极界面结构通过在硅基底背面钝化层上设置不连续的接触开口并使碳基种子层连续覆盖于开口内及钝化层表面,实现了在接触开口区域内碳基种子层与硅掺杂区直接形成欧姆接触界面,从而保障电极与硅基底之间的低阻电学连接;同时,在钝化层表面区域,碳基种子层借助玻璃相冷却收缩形成的微结构实现机械锚定界面,显著提升种子层与钝化层之间的结合强度和界面稳定性;该结构设计兼顾了电学导通功能与力学附着功能,并有利于缓解因热膨胀系数差异引起的界面应力积累。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122995338A_ABST
    Figure CN122995338A_ABST
Patent Text Reader

Abstract

The application provides a back contact solar cell electrode interface structure based on a carbon-based seed layer and a preparation method thereof, and relates to the technical field of solar energy. The electrode interface structure comprises a silicon substrate, a carbon-based seed layer and a conductive layer. The back surface of the silicon substrate is provided with a passivation layer, and the passivation layer is distributed with discontinuous contact openings to expose the underlying silicon doped region. The carbon-based seed layer continuously covers the surface of the passivation layer and the inside of the openings. The conductive layer is arranged on the surface of the seed layer. In the contact openings, the carbon-based seed layer forms an ohmic contact interface with the silicon substrate to ensure low-resistance electrical connection. On the surface of the passivation layer, the carbon-based seed layer forms a mechanical anchoring interface through glass phase cooling and shrinkage to improve the bonding strength and interface stability. The electrode interface structure of the application breaks through the technical bottleneck that carbon materials are difficult to realize ohmic contact and reliable adhesion in crystalline silicon cells, and has the advantages of low cost, low stress, easy printing integration and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solar cell technology, and in particular to a back-contact solar cell electrode interface structure based on a carbon-based seed layer and its preparation method. Background Technology

[0002] Back-contact solar cells place both the positive and negative electrodes on the back of the silicon substrate, achieving zero shading on the front side. This is one of the important technical routes for improving the photoelectric conversion efficiency of crystalline silicon solar cells. In the metallization process, the "printed conductive seed layer - electroplated copper thickening" scheme can significantly reduce the amount of expensive silver paste used and improve the overall conductivity of the electrodes, which has become a key direction for current industry research and industrialization.

[0003] However, the existing technology still has the following shortcomings: (1) Limited selection of seed layer materials: Currently, the mainstream seed layer is still mainly silver paste, which has prominent cost pressure; although base metal seed layers such as nickel and copper have been explored, nickel has problems such as high internal stress, high porosity, and thermal expansion coefficient mismatch with silicon; although titanium has good conductivity and corrosion resistance, can form low-resistivity silicide with silicon, and can be used as a copper diffusion barrier layer, it is very easy to oxidize in air to form a high-resistivity oxide layer, which makes it difficult to prepare by conventional printing and sintering process, and cannot meet the strict requirements of electroplating seed layer for surface conductivity and activity. (2) Carbon-based seed layers have not yet been applied to crystalline silicon cells: Carbon paste has been used in perovskite solar cells and has advantages such as extremely low cost and good chemical stability; however, due to the high intrinsic resistivity of carbon materials and the difficulty in forming low-resistivity ohmic contact with silicon substrate, it has not yet been used as a seed layer in crystalline silicon back contact solar cells. (3) The problem of interface stress has not been solved: Due to the difference in thermal expansion coefficients between the continuous metal grid lines and the silicon substrate, significant thermomechanical stress is generated during multiple heat treatments (such as seed layer sintering, copper layer sintering or electroplating followed by annealing), which can easily induce microcracks in the cell and affect the long-term reliability of the module.

[0004] Therefore, developing a carbon-based seed layer material that can meet electrical performance requirements and is compatible with printing and sintering processes, and combining it with structural design to effectively release interfacial stress, has become a technical problem that urgently needs to be solved in this field.

[0005] In view of this, the present invention is hereby proposed. Summary of the Invention

[0006] The primary objective of this invention is to provide a back-contact solar cell electrode interface structure based on a carbon-based seed layer. This solar cell electrode interface structure achieves ohmic contact between the carbon-based seed layer and the silicon substrate within the contact openings through a synergistic design of discontinuous contact openings and continuous carbon-based seed layer coverage. On the passivation layer surface, the carbon-based seed layer is mechanically anchored by the glass phase. This effectively alleviates the interface stress caused by thermal expansion coefficient mismatch while ensuring low contact resistance and high interface adhesion.

[0007] The second objective of this invention is to provide a method for preparing a back-contact solar cell electrode interface structure based on a carbon-based seed layer.

[0008] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted: The present invention provides a back contact solar cell electrode interface structure based on a carbon-based seed layer, the electrode interface structure comprising: a silicon substrate, a carbon-based seed layer, and a conductive layer; A passivation layer is provided on the back side of the silicon substrate, and the passivation layer has discontinuous contact openings that expose the silicon doped region on the back side of the silicon substrate. The carbon-based seed layer continuously covers the surface of the passivation layer and the contact opening; The conductive layer is disposed on the surface of the carbon-based seed layer; Wherein: within the contact opening, the carbon-based seed layer forms an ohmic contact interface with the silicon substrate; on the surface of the passivation layer, the carbon-based seed layer forms a mechanical anchoring interface through a glass phase.

[0009] Furthermore, the contact openings are distributed in a dot matrix pattern or a groove array pattern; Preferably, when the contact openings are arranged in a dot matrix pattern, the size of a single contact opening is 10-50 μm, and the center-to-center distance between adjacent contact openings is 50-200 μm. Preferably, when the trenches are distributed in an array, the length of a single trench of the contact opening is 50~200μm, the width is 10~30μm, and the spacing between adjacent trenches is 20~100μm; Preferably, the thickness of the passivation layer is 50~150 nm; Preferably, the thickness of the carbon-based seed layer is 1~3 μm; Preferably, the conductive layer is formed by electroplating copper or printing copper paste, and has a thickness of 5~15μm; Preferably, the thickness of the carbon-based seed layer at the contact opening is greater than the thickness on the surface of the passivation layer, and the thickness difference is 5-15%.

[0010] Furthermore, the carbon-based seed layer is formed by printing and heat treatment of carbon-based paste; Preferably, by weight, the carbon-based slurry comprises: 50-90 parts of carbon-based conductive powder, 1-10 parts of glass powder, and 10-40 parts of organic carrier solution.

[0011] Furthermore, the carbon-based conductive powder is selected from one or more of carbon powder, graphene, carbon nanotubes, and conductive carbon black. Preferably, the glass powder is lead-free glass powder, and the softening temperature of the lead-free glass powder is 300~550℃, and the particle size is 0.1~5μm; Preferably, the organic carrier solution is selected from one or more of terpineol, ethyl cellulose, ethylene glycol ethyl ether acetate, tributyl citrate, and dibutyl phthalate.

[0012] Furthermore, the carbon-based conductive powder has a dual particle size distribution, including: micron-sized carbon powder with a particle size of 1~10μm and nano-sized carbon powder with a particle size of 20~200nm. Among them, micron-sized carbon powder accounts for 60-80 wt% of the total weight of carbon-based conductive powder, and nano-sized carbon powder accounts for 20-40 wt%.

[0013] Furthermore, the carbon-based slurry also contains additives; Preferably, the additive includes one or more of dispersants, leveling agents, defoamers, and coupling agents; Preferably, the additive accounts for 0.1 to 1 part by weight in the carbon-based slurry.

[0014] Furthermore, the electrode interface structure also includes a contact layer; The contact layer is located inside the contact opening, between the carbon-based seed layer and the silicon substrate, and covers the bottom and sidewalls of the contact opening; Preferably, the contact layer is formed by physical deposition; Preferably, the contact layer is a silver contact layer formed by physical deposition.

[0015] Preferably, the thickness of the contact layer is 10~200nm.

[0016] The present invention provides a method for preparing the above-mentioned electrode interface structure, the method comprising: (a) A back-contact solar cell silicon substrate with a passivation layer on the back side is provided, wherein discontinuous contact openings are formed on the passivation layer to expose silicon doped regions of the underlying silicon substrate; (b) Print carbon-based paste onto the back side of a silicon substrate to form a continuous wet paste film covering the opening area and the surface of the passivation layer, and heat-treat to form a carbon-based seed layer; (c) A conductive layer is formed on the surface of the seed layer to obtain a metallized electrode structure.

[0017] Optionally, the preparation method further includes, prior to step (b), forming a contact layer within the contact opening by physical deposition.

[0018] Furthermore, the contact opening in (a) is prepared by a laser opening method. After laser opening, the passivation layer at the bottom of the contact opening area is completely removed, exposing the silicon doped region.

[0019] Furthermore, the heat treatment method in (b) includes: Treat at 200-400℃ for 5-30 minutes under a protective atmosphere.

[0020] Compared with the prior art, the beneficial effects of the present invention are as follows: The present invention provides a back-contact solar cell electrode interface structure based on a carbon-based seed layer. This electrode interface structure achieves a direct ohmic contact interface between the carbon-based seed layer and the silicon doped region within the contact opening area by setting discontinuous contact openings on the passivation layer on the back of a silicon substrate and continuously covering the openings and the passivation layer surface with a carbon-based seed layer. This ensures a low-resistance electrical connection between the electrode and the silicon substrate. Simultaneously, in the passivation layer surface region, the carbon-based seed layer achieves mechanical anchoring of the interface through microstructures formed by the cooling and contraction of the glass phase, significantly improving the bonding strength and interface stability between the seed layer and the passivation layer. This structural design balances electrical conductivity and mechanical adhesion, and helps alleviate the accumulation of interface stress caused by differences in thermal expansion coefficients.

[0021] The present invention provides a method for preparing an electrode interface structure. The method involves preparing discontinuous contact openings on a passivation layer, printing carbon-based paste and performing heat treatment to form a continuous seed layer, and then constructing a conductive layer on the seed layer. This method achieves controllable interface reaction and integration between the carbon-based seed layer, the silicon substrate, and the passivation layer. Attached Figure Description

[0022] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0023] Figure 1 This is a schematic cross-sectional view of the back contact solar cell electrode interface structure provided in Embodiment 4 of the present invention; Figure 2 This is a top view of the dot matrix opening pattern on the back side of the back contact solar cell provided in Embodiment 4 of the present invention; Figure 3This is a top view of the back trench array opening pattern of the back contact solar cell provided in Embodiment 5 of the present invention.

[0024] Icons: 1-Silicon substrate; 2-Passivation layer; 3-Contact opening; 4-Seed layer; 5-Conductive layer; 6-Contact layer. Detailed Implementation

[0025] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0026] According to one aspect of the present invention, a back contact solar cell electrode interface structure based on a carbon-based seed layer 4 is provided, the electrode interface structure comprising: a silicon substrate 1, a carbon-based seed layer 4, and a conductive layer 5. A passivation layer 2 is provided on the back side of the silicon substrate 1, and a discontinuous contact opening 3 is provided on the passivation layer 2, the contact opening 3 exposing the silicon doped region on the back side of the silicon substrate 1. The carbon-based seed layer 4 continuously covers the surface of the passivation layer 2 and the inside of the contact opening 3; The conductive layer 5 is disposed on the surface of the carbon-based seed layer 4; Wherein: within the contact opening 3, the carbon-based seed layer 4 forms an ohmic contact interface with the silicon substrate 1; on the surface of the passivation layer 2, the carbon-based seed layer 4 forms a mechanical anchoring interface through a glass phase.

[0027] The present invention provides a back-contact solar cell electrode interface structure based on a carbon-based seed layer 4. This electrode interface structure achieves a direct ohmic contact interface between the carbon-based seed layer 4 and the silicon doped region within the contact opening 3 region by setting discontinuous contact openings 3 on the passivation layer 2 on the back side of the silicon substrate 1 and continuously covering the openings and the surface of the passivation layer 2 with the carbon-based seed layer 4. This ensures a low-resistance electrical connection between the electrode and the silicon substrate 1. Simultaneously, in the passivation layer 2 surface region, the carbon-based seed layer 4 achieves mechanical anchoring of the interface through the microstructure formed by the cooling and shrinkage of the glass phase, significantly improving the bonding strength and interface stability between the seed layer 4 and the passivation layer 2. This structural design balances electrical conductivity and mechanical adhesion, and helps alleviate the accumulation of interface stress caused by differences in thermal expansion coefficients.

[0028] In a preferred embodiment of the present invention, the contact openings 3 are distributed in a dot matrix pattern or in a trench array pattern. As a preferred embodiment, the contact openings 3 are distributed in a dot matrix or a trench array, which can effectively disperse the thermomechanical stress between the metal and silicon while achieving local electrical contact with the silicon substrate 1, reducing the risk of microcracks in the cell, and facilitating the uniform filling of the seed layer 4 slurry in the opening area and continuous coverage on the surface of the passivation layer 2.

[0029] In the preferred embodiment described above, when the dot matrix distribution is used, the size of a single contact opening 3 is 10~50μm, for example, it can be 10μm, 20μm, 30μm, 40μm or 50μm; the center-to-center distance between adjacent contact openings 3 is 50~200μm, for example, it can be 50μm, 100μm, 150μm or 200μm; each size and distance value can also be any continuous value within the corresponding range.

[0030] In the preferred embodiment described above, when the trenches are distributed in an array, the length of a single trench is 50~200μm, for example, 50μm, 100μm, 150μm or 200μm; the width is 10~30μm, for example, 10μm, 15μm, 20μm, 25μm or 30μm; the spacing between adjacent trenches is 20~100μm, for example, 20μm, 40μm, 60μm, 80μm or 100μm; and each dimensional parameter can also be any continuous value within the corresponding range.

[0031] In a preferred embodiment of the present invention, the passivation layer 2 has a thickness of 50~150nm; the carbon-based seed layer 4 has a thickness of 1~3μm; and the conductive layer 5 is formed by electroplating copper or printing copper paste, with a thickness of 5~15μm. In a preferred embodiment, the passivation layer 2 has a thickness of 50~150 nm, which helps to ensure the surface passivation effect while taking into account the controllability of the laser opening process; the carbon-based seed layer 4 has a thickness of 1~3 μm, which can fully form the metal-silicon alloy ohmic contact layer 6 in the contact opening 3 and achieve effective glass phase anchoring on the surface of the passivation layer 2; the conductive layer 5 has a thickness of 5~15 μm, which can meet the electrode conductivity requirements and support the mechanical strength requirements of subsequent welding and component packaging.

[0032] In a preferred embodiment of the present invention, the thickness of the carbon-based seed layer 4 at the contact opening 3 is greater than the thickness on the surface of the passivation layer 2, and the thickness difference is 5-15%.

[0033] In a preferred embodiment, the thickness of the carbon-based seed layer 4 at the contact opening 3 is greater than the thickness on the surface of the passivation layer 2. This allows the carbon-based seed layer 4 to have a more sufficient material filling amount in the contact opening 3 region, which is beneficial to enhance its physical contact area and interfacial bonding tightness with the silicon doped region, thereby optimizing the ohmic contact performance.

[0034] In a preferred embodiment of the present invention, the carbon-based seed layer 4 is formed by printing and heat treatment of carbon-based paste; As an optional implementation, the carbon-based slurry comprises, by weight, 50-90 parts of carbon-based conductive powder, for example, 50, 60, 70, 80, or 90 parts, or any value between 50 and 90 parts; 1-10 parts of glass powder, for example, 1, 3, 5, 7, or 10 parts, or any value between 1 and 10 parts; and 10-40 parts of organic carrier solution, for example, 10, 20, 30, or 40 parts, or any value between 10 and 40 parts.

[0035] In a preferred embodiment of the present invention, the carbon-based conductive powder is selected from one or more of carbon powder, graphene, carbon nanotubes, and conductive carbon black; In a preferred embodiment of the present invention, the glass powder is lead-free glass powder, the softening temperature of the lead-free glass powder is 300~550℃, and the particle size is 0.1~5μm; As a preferred embodiment, the present invention uses lead-free glass powder with a softening temperature range of 300~550℃, which can fully soften and wet the surface microstructure of the passivation layer 2 during the medium temperature stage of sintering, forming a uniform and stable glass phase anchoring layer, while avoiding excessive flow or volatilization at high temperature, which is beneficial to maintaining the morphological integrity and interfacial bonding stability of the seed layer 4.

[0036] In a preferred embodiment of the present invention, the organic carrier solution is selected from one or more of terpineol, ethyl cellulose, ethylene glycol ethyl ether acetate, tributyl citrate, and dibutyl phthalate.

[0037] In a preferred embodiment of the present invention, the carbon-based conductive powder comprises a dual particle size distribution, including: micron-sized carbon powder with a particle size of 1~10μm and nano-sized carbon powder with a particle size of 20~200nm. Among them, micron-sized carbon powder accounts for 60-80 wt% of the total weight of carbon-based conductive powder, and nano-sized carbon powder accounts for 20-40 wt%.

[0038] As a preferred embodiment, the carbon-based conductive powder of the present invention adopts a dual particle size distribution, which can form a dense stacked structure in the slurry, ensuring the rheological stability and formability of the printed wet film, and enhancing the interfacial reactivity through nano-scale powder, thus promoting the uniform generation of the interface within the contact opening 3.

[0039] In a preferred embodiment of the present invention, the carbon-based slurry further comprises additives, including one or more of dispersants, leveling agents, defoamers, and coupling agents; Preferably, the additive accounts for 0.1 to 1 part by weight in the carbon-based slurry.

[0040] In a preferred embodiment, the additives in the carbon-based slurry of the present invention include one or more of dispersants, leveling agents, defoamers, and coupling agents, which help to improve the uniform dispersion of each component of the slurry, the leveling performance during the printing process, and the surface quality of the wet film, reduce printing defects, and improve the coverage integrity and interface bonding consistency of the seed layer 4 in the passivation layer 2 and the contact opening 3 area.

[0041] In a preferred embodiment of the present invention, the electrode interface structure further includes a contact layer 6, which is located inside the contact opening 3, between the carbon-based seed layer 4 and the silicon substrate 1, and covers the bottom and sidewalls of the contact opening 3. In a preferred embodiment, the contact layer 6 of the present invention is disposed between the carbon-based seed layer 4 and the silicon substrate 1 within the contact opening 3, and covers the bottom and sidewalls of the opening. This can create a more reliable electrical connection channel between the carbon-based seed layer 4 and the silicon substrate 1, further reduce the interface contact resistance, and improve the carrier collection efficiency.

[0042] In the preferred embodiment described above, the contact layer 6 is a silver contact layer formed by physical deposition. Preferably, the thickness of the contact layer 6 is 10~200nm.

[0043] According to one aspect of the present invention, a method for preparing the above-described electrode interface structure, the method comprising: (a) A back-contact solar cell silicon substrate 1 with a passivation layer 2 on the back is provided, wherein discontinuous contact openings 3 are formed on the passivation layer 2 to expose the silicon doped region of the underlying silicon substrate 1; (b) Print carbon-based paste onto the back side of silicon substrate 1 to form a continuous wet paste film covering the opening area and the surface of passivation layer 2, and heat-treat to form carbon-based seed layer 4; (c) A conductive layer 5 is formed on the surface of the seed layer 4 to obtain a metallized electrode structure.

[0044] The present invention provides a method for preparing an electrode interface structure. The method involves preparing discontinuous contact openings 3 on a passivation layer 2, printing carbon-based paste and performing heat treatment to form a continuous seed layer 4, and then constructing a conductive layer 5 on the seed layer 4. This method achieves controllable interface reaction and integration between the carbon-based seed layer 4, the silicon substrate 1, and the passivation layer 2.

[0045] In a preferred embodiment of the present invention, the preparation method further includes a step of forming a contact layer 6 in the contact opening 3 by physical deposition before step (b).

[0046] In a preferred embodiment of the present invention, the contact opening 3 in (a) is prepared by a laser opening method. After laser opening, the passivation layer 2 at the bottom of the contact opening 3 region is completely removed, exposing the silicon doped region.

[0047] In a preferred embodiment, the present invention uses a laser-based opening method to prepare the contact opening 3, and ensures that the passivation layer 2 is completely removed to expose the clean silicon surface. At the same time, it controls the alignment accuracy between the opening position and the silicon doped region below, which is beneficial to forming a uniform, low-resistance metal-silicon alloy ohmic contact in the opening area and avoids leakage or contact failure caused by misalignment.

[0048] In a preferred embodiment of the present invention, the heat treatment method in (b) includes: treating at 200~400°C for 5~30 min under a protective atmosphere.

[0049] As an optional implementation, the heat treatment temperature is 200~400℃, for example, it can be 200℃, 250℃, 300℃, 350℃, 400℃, or any temperature value between 200~400℃; the heat treatment time is 5~30 minutes, for example, it can be 5 min, 10 min, 15 min, 20 min, 25 min, 30 min, or any time value between 5~30 minutes.

[0050] The technical solution of the present invention will be further described below with reference to the embodiments.

[0051] Examples 1-3 A method for fabricating a back-contact solar cell electrode interface structure based on a carbon-based seed layer 4 includes the following steps: (1) Provide completed texturing and phosphorus expansion (n + (area), boron expansion (p) + (region), stacked passivation (SiN) x / AlO x The back contact solar cell silicon substrate 1 of the process, wherein the passivation layer 2 has a thickness of 100 nm; (2) Dot-matrix opening: A nanosecond pulsed fiber laser with a wavelength of 1064 nm was used for the opening process. Dot-matrix distributed circular contact openings 3 were prepared on the passivation layer 2, wherein the diameter of a single opening was 30 μm and the center-to-center distance between adjacent openings was 100 μm. The laser process parameters were set as follows: single pulse energy 80 μJ, scanning speed 1000 mm / s, and spot overlap rate 70%. The passivation layer 2 at the bottom of the opening area was completely removed, exposing a clean n + The silicon surface is doped and there is no melting or thermal damage to the silicon substrate 1; (3) Preparation of carbon-based slurry: see Table 1 for the parts by weight.

[0052] Table 1:

[0053] The above raw materials were stirred and degassed in a vacuum mixer at 30°C for 30 min to obtain a uniform carbon-based slurry.

[0054] Note: In Examples 1-3, the "carbon-based conductive powder" (carbon powder) has a dual particle size distribution, wherein the micron-sized carbon powder with a particle size of 1-10 μm accounts for 75 wt% of the total weight of the carbon-based conductive powder, and the nano-sized carbon powder with a particle size of 20-200 nm accounts for 25 wt%; the lead-free glass powder is a bismuth-boron-zinc glass powder with a softening temperature of 420℃ and a particle size of 0.3 μm.

[0055] (4) The carbon-based paste of this embodiment was printed using a single-filament thin screen printing plate with a mesh size of 325, and the wet film thickness was controlled to be 4μm; Subsequently, the mixture was treated at 300°C for 20 minutes in a nitrogen-protected atmosphere furnace and then naturally cooled to room temperature to form a carbon-based seed layer 4. The measured thickness of the seed layer 4 within the contact opening 3 is 1.98 μm, and the thickness on the surface of the passivation layer 2 is 1.8 μm, with a thickness difference of 10%. (5) Electroplating is performed on the surface of the carbon-based seed layer 4 using an acidic copper sulfate electroplating solution with a current density of 2 A / dm² and an electroplating time of 25 min to obtain a copper conductive layer 5 with a thickness of 10 μm, which forms a metallized electrode grid line, thus obtaining the electrode interface structure.

[0056] Example 4 Figure 1 This is a schematic cross-sectional view of the back contact solar cell electrode interface structure provided in Embodiment 4 of the present invention; Figure 2 This is a top view of the dot matrix opening pattern on the back side of the back contact solar cell provided in Embodiment 4 of the present invention; This embodiment is basically the same as Embodiment 1, except that: After laser drilling is completed in step (2) and before printing carbon-based paste in step (3), the following steps are added: (2a) Physical deposition of contact layer 6: The silicon substrate 1 with the laser-opened section is placed in the magnetron sputtering chamber and the vacuum is evacuated to below 5 × 10⁻⁶. -4 After Pa, high-purity argon gas (purity ≥99.999%) was introduced and the sputtering pressure was maintained at 0.8 Pa. A high-purity silver target (purity ≥99.99%) was used as the target material, and a DC power supply was used with the sputtering power set to 100W. Before sputtering, the silver target was pre-sputtered for 10 minutes to remove oxides from the target surface. Deposition was carried out at room temperature, and the sputtering time was controlled to achieve a silver layer thickness of 120 nm. After deposition, the silver layer was naturally cooled to room temperature in a vacuum chamber before being removed.

[0057] The remaining steps (3) to (5) are the same as in Example 1.

[0058] Example 5 Figure 3 This is a top view of the back trench array opening pattern of the back contact solar cell provided in Embodiment 5 of the present invention.

[0059] A method for fabricating a back-contact solar cell electrode interface structure based on a carbon-based seed layer 4 includes the following steps: (1) Same as Example 1; (2) A nanosecond laser with a wavelength of 532 nm (pulse width of 15 ns) was used to prepare contact openings 3 in a trench array on the passivation layer 2. The specific parameters are as follows: Single trench length: 200μm; trench width: 30μm; spacing between adjacent trenches: 100μm; Laser energy density: 4.5 J / cm²; scanning speed: 100 mm / s; repetition rate: 500 kHz.

[0060] Actual test results: passivation layer 2 was completely removed, and the surface roughness Ra of the silicon at the bottom of the trench was less than 2.5 nm; the alignment accuracy error was less than 5.8 μm.

[0061] (3)~(5): Same as Example 1.

[0062] Example 6 The difference between this embodiment and embodiment 1 is that the size of a single opening of contact opening 3 in step "(2) dot matrix opening" is 80μm, and the rest is the same as in embodiment 1, as follows: (2) Dot matrix opening: A picosecond laser with a wavelength of 355nm is used to perform the opening process. Dot matrix distributed contact openings 3 are prepared on the passivation layer 2, wherein the diameter of a single opening is 80μm and the center-to-center distance between adjacent openings is 120μm.

[0063] Example 7 The difference between this embodiment and embodiment 1 is that step (4) is different from that in embodiment 1, but the rest is the same as in embodiment 1, as follows: (4) The paste A was printed using a 325 mesh screen, the wet film thickness was controlled to be 4 μm, and the film was kept at 480℃ for 5 min in N2 atmosphere to form seed layer 4.

[0064] Example 8 The difference between this comparative example and Example 1 is that the weight of glass powder in step "(3) preparing carbon-based slurry" is 0 parts, while the rest is the same as in Example 1. See Table 2 for details.

[0065] Table 2:

[0066] The above raw materials were stirred and degassed in a vacuum mixer at 30°C for 30 min to obtain a uniform carbon-based slurry.

[0067] Example 9 The difference between this comparative example and Example 1 is that the carbon conductive powder (carbon powder) in step "(3) preparing carbon-based slurry" has a single particle size distribution and all carbon powder with a particle size of 5μm is used. The rest is the same as in Example 1.

[0068] Comparative Example 1 The difference between this comparative example and Example 1 is that the carbon-based paste in step (3) is replaced with commercially available silver paste on the back of a solar cell as the seed layer 4. Specifically, the commercially available back silver paste for solar cells is Heraeus SOL205B back silver paste, which contains 80 parts silver powder, 8 parts glass powder, and 12 parts organic carrier. Subsequently, a seed layer 4 wet film was formed by screen printing (325 mesh), dried at 220°C, and sintered at a peak temperature of 800°C to form a silver seed layer 4 with a thickness of 4μm. Then, copper was electroplated to thicken the layer and form an electrode.

[0069] Experimental Example 1 The solar cells used in this experiment are of the G12R size (182mm × 210mm, diagonal length 295mm), with a single cell area of ​​approximately 382cm². This size is one of the mainstream large-size specifications in the photovoltaic industry, and the test results are representative of the industry.

[0070] This experimental example is used to verify the technical effectiveness of the metallized electrode structure in Examples 1-5 and Comparative Example 1. The specific test methods are as follows: (1) Metal electrode contact resistivity test: Using the transmission line model (TLM) method, several sample strips of equal width were prepared by cutting the solar cell along the direction perpendicular to the grid line. The total resistance between adjacent grid lines was measured in a dark room environment, and the resistance versus spacing curve was plotted. The contact resistivity of the metal electrode (mΩ•cm²) was calculated by linear fitting.

[0071] (2) Welding tensile test: After depositing a tin layer on the copper grid line, the tin-plated solder strip is soldered to the main grid of the solar cell using a soldering station set at a temperature of 300~350℃. After the sample cools to room temperature, the solder strip is peeled off vertically using a tensile testing machine at a peel angle of 90° or 180° and a constant speed of 50~100 mm / min. The steady-state force value during the peeling process is recorded and the ratio of the force value to the grid line width is taken. Twelve solder joints are tested for each sample, and the average value (N / mm) is taken.

[0072] (3) Electrical performance (photoelectric conversion efficiency, open circuit voltage, etc.) testing; Under standard test conditions (STC: AM1.5 spectrum, 1000 W / m² irradiance, 25℃), the current-voltage characteristic curve of the battery was measured, and the above parameters were extracted.

[0073] The specific test results are shown in Table 3.

[0074] Table 3:

[0075] As shown in Table 3 above, Example 1, using a carbon-based paste (70 parts carbon powder, 5 parts glass powder, and 20 parts carrier), achieved a conversion efficiency of 25.6% and an open-circuit voltage of 734 mV, with a welding pull force of 2.4 N / mm, without using silver at all. This is superior to the silver paste in Comparative Example 1 (25.2%, 731 mV, 2.5 N / mm). This indicates that the carbon-based seed layer 4, through the synergistic effect of dual-particle-size filling densification and glass phase anchoring, can completely replace silver paste and achieve superior performance.

[0076] In Example 2 (50 parts toner), the efficiency dropped to 24.2% due to the low content of toner and glass powder, resulting in an incomplete conductive network and insufficient interface anchoring. In Example 3 (90 parts toner and 10 parts glass powder), the efficiency was 24.8% due to the excessive introduction of insulating phase by glass powder, which hindered conductive contact. Both were lower than in Example 1, proving that 70 parts toner, 5 parts glass powder, and 20 parts carrier are the optimal ratio.

[0077] In Example 4, a 120nm physically deposited thin silver layer was added between the carbon-based seed layer 4 and the silicon substrate 1. The contact resistivity was significantly reduced from 2.2mΩ·cm² to 1.0mΩ·cm², the conversion efficiency was increased to 26.2%, and the open-circuit voltage was increased to 738mV, all of which were the best values ​​among all examples. This result demonstrates that the synergistic mechanism of the low-resistance ohmic contact of silver / silicon and the lateral conductivity of the carbon layer can compensate for the inherent defect of high interface resistance between carbon-based materials and silicon, while retaining the low cost and corrosion resistance advantages of the carbon layer. Moreover, the amount of 120nm silver layer used is only 1 / 50 to 1 / 80 of that of traditional silver paste, resulting in a very limited increase in cost.

[0078] Example 5, which uses a trench array aperture (conversion efficiency 25.4%, open circuit voltage 732mV), has performance that is basically equivalent to that of the dot matrix aperture (25.6%, 734mV) in Example 1, indicating that the carbon-based seed layer 4 scheme of the present invention has good process adaptability to different aperture patterns.

[0079] In Example 6, when the opening size was increased to 80 μm, the conversion efficiency dropped to 25.0% and the welding pull force dropped to 2.1 N / mm. This indicates that an excessively large opening size will lead to a decrease in the uniformity of filling and covering of the carbon-based seed layer 4 in the opening area and an increase in contact interface defects.

[0080] Example 7 used single-stage isothermal sintering (480℃ / 5min) instead of the segmented sintering in Example 1. The conversion efficiency decreased from 25.6% to 24.6%, the open-circuit voltage decreased from 734mV to 726mV, and the welding tensile force decreased from 2.4N / mm to 1.6N / mm. This result demonstrates the necessity of the segmented sintering process.

[0081] In Example 8, after removing the glass powder, the welding pull force plummeted from 2.4 N / mm to 0.6 N / mm (a decrease of 75%), the contact resistivity increased to 7.8 mΩ·cm², the efficiency decreased from 25.6% to 19.7%, and the open-circuit voltage dropped to 683 mV. This demonstrates that the mechanical anchoring of the glass phase on the surface of the passivation layer 2 is a necessary feature to ensure interfacial bonding strength and maintain low contact resistance; without glass powder, the interface cannot form effective anchoring, and delamination is easy under thermal stress and peeling force. Microscopic voids lead to current obstruction and severe performance degradation.

[0082] In Example 9, after replacing the carbon powder with a single particle size (5 μm), the efficiency dropped to 21.5%, the open-circuit voltage dropped to 699 mV, and the welding pull force dropped to 1.2 N / mm. This demonstrates that a single particle size cannot effectively fill the interparticle gaps, resulting in high porosity and poor conductivity in seed layer 4. The dual-particle-size distribution of nano-carbon powder fills the gaps between micron-sized carbon powder, increasing the packing density and contact area, which is key to achieving high density and stable ohmic contact.

[0083] Comparative Example 1 used commercially available silver paste (Heraeste SOL205B) as seed layer 4, with a contact resistivity of only 0.8 mΩ·cm², demonstrating excellent ohmic contact characteristics between silver and silicon. However, the conversion efficiencies of Example 1 (pure carbon-based, 25.6%) and Example 4 (carbon-based combined with a thin silver layer, 26.2%) were both superior to Comparative Example 1 (25.2%), with Example 4 showing a 1.0 percentage point higher efficiency and a 7 mV higher open-circuit voltage than Comparative Example 1. The above comparisons demonstrate that the present invention, through the synergistic design of a carbon-based seed layer 4 and an optional ultrathin silver layer, can achieve conversion efficiencies superior to commercially available silver paste solutions even without using silver or with only a very small amount of silver.

[0084] In summary, this invention achieves completely silver-free fabrication of back-contact solar cell electrodes through the synergistic design of carbon-based seed layer 4 and segmented sintering process. Moreover, the overall electrical performance and interface reliability are superior to commercially available silver paste solutions, providing a feasible material and process solution for cost reduction and efficiency improvement of photovoltaic cells.

[0085] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A back-contact solar cell electrode interface structure based on a carbon-based seed layer, characterized in that, The electrode interface structure includes: a silicon substrate, a carbon-based seed layer, and a conductive layer; A passivation layer is provided on the back side of the silicon substrate, and the passivation layer has discontinuous contact openings that expose the silicon doped region on the back side of the silicon substrate. The carbon-based seed layer continuously covers the surface of the passivation layer and the contact opening; The conductive layer is disposed on the surface of the carbon-based seed layer; Wherein: within the contact opening, the carbon-based seed layer forms an ohmic contact interface with the silicon substrate; on the surface of the passivation layer, the carbon-based seed layer forms a mechanical anchoring interface through a glass phase.

2. The electrode interface structure according to claim 1, characterized in that, The contact openings are distributed in a dot matrix pattern or a groove array pattern. Preferably, when the contact openings are arranged in a dot matrix pattern, the size of a single contact opening is 10-50 μm, and the center-to-center distance between adjacent contact openings is 50-200 μm. Preferably, when the trenches are distributed in an array, the length of a single trench of the contact opening is 50~200μm, the width is 10~30μm, and the spacing between adjacent trenches is 20~100μm; Preferably, the thickness of the passivation layer is 50~150 nm; Preferably, the thickness of the carbon-based seed layer is 1~3 μm; Preferably, the conductive layer is formed by electroplating copper or printing copper paste, and has a thickness of 5~15μm; Preferably, the thickness of the carbon-based seed layer at the contact opening is greater than the thickness on the surface of the passivation layer, and the thickness difference is 5-15%.

3. The electrode interface structure according to claim 1, characterized in that, The carbon-based seed layer is formed by printing and heat treatment of carbon-based paste; Preferably, by weight, the carbon-based slurry comprises: 50-90 parts of carbon-based conductive powder, 1-10 parts of glass powder, and 10-40 parts of organic carrier solution.

4. The electrode interface structure according to claim 3, characterized in that, The carbon-based conductive powder is selected from one or more of carbon powder, graphene, carbon nanotubes, and conductive carbon black. Preferably, the glass powder is lead-free glass powder, and the softening temperature of the lead-free glass powder is 300~550℃, and the particle size is 0.1~5μm; Preferably, the organic carrier solution is selected from one or more of terpineol, ethyl cellulose, ethylene glycol ethyl ether acetate, tributyl citrate, and dibutyl phthalate.

5. The electrode interface structure according to claim 3, characterized in that, The carbon-based conductive powder has a dual particle size distribution, including: micron-sized carbon powder with a particle size of 1~10μm and nano-sized carbon powder with a particle size of 20~200nm. Among them, micron-sized carbon powder accounts for 60-80 wt% of the total weight of carbon-based conductive powder, and nano-sized carbon powder accounts for 20-40 wt%.

6. The electrode interface structure according to claim 3, characterized in that, The carbon-based slurry also contains additives; Preferably, the additive includes one or more of dispersants, leveling agents, defoamers, and coupling agents; Preferably, the additive accounts for 0.1 to 1 part by weight in the carbon-based slurry.

7. The electrode interface structure according to claim 1, characterized in that, The electrode interface structure further includes a contact layer; The contact layer is located inside the contact opening, between the carbon-based seed layer and the silicon substrate, and covers the bottom and sidewalls of the contact opening; Preferably, the contact layer is formed by physical deposition; Preferably, the thickness of the contact layer is 10~200nm.

8. A method for preparing an electrode interface structure according to any one of claims 1 to 7, characterized in that, The preparation method includes: (a) A back-contact solar cell silicon substrate with a passivation layer on the back side is provided, wherein discontinuous contact openings are formed on the passivation layer to expose silicon doped regions of the underlying silicon substrate; (b) Print carbon-based paste onto the back side of a silicon substrate to form a continuous wet paste film covering the opening area and the surface of the passivation layer, and heat-treat to form a carbon-based seed layer; (c) A conductive layer is formed on the surface of the carbon-based seed layer to obtain a metallized electrode structure; Optionally, the preparation method further includes, prior to step (b), forming a contact layer within the contact opening by physical deposition.

9. The method for preparing the electrode interface structure according to claim 8, characterized in that, The contact opening in (a) is prepared by a laser opening method. After laser opening, the passivation layer at the bottom of the contact opening area is completely removed, exposing the silicon doped region.

10. The method for preparing the electrode interface structure according to claim 8, characterized in that, The heat treatment method in (b) includes: Treat at 200-400℃ for 5-30 minutes under a protective atmosphere.